PENGEMBANGAN MODUL PEMBELAJARAN TEKNIK PERBAIKAN DAN PERAWATAN PERANGKAT ELEKTRONIKA AUDIO VIDEO BERBASIS STAD SISWA KELAS XII SMKN 5 SURABAYA - Aris Basuki (Khazanah Pendidikan, 2020)
ABSTRACTThis research is a research and development study using the ADDIE model whichincludes stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5)Evaluation. The purpose of this study was to produce teaching materials in the form ofengineering modules for the repair and maintenance of audio-based electronic videoequipment based on STAD grade XII students of SMK Negeri 5 Surabaya. Moduledevelopment is based on an analysis of the needs and characteristics of students ofSMK Negeri 5 Surabaya.Material/content experts give validation of 83.13%, learningdesign experts give validation of 76.67%, individual trials get a percentage of 81.00%,small group trials get a percentage of 80.33%, field trials get a percentage 77.45%,and teacher assessment in the field of audio-video electronics engineering gave apercentage of 85.62%. Based on the level of achievement converted into 5 scales, itcan be concluded that the development of learning modules meets the criteria well.STAD based module learning is effective learning. Classical learning completeness hasbeen achieved, 25 of 30 students (83.33%) have achieved mastery learning. Thedevelopment of an engineering module for the improvement and maintenance of STADbased audio-video electronic devices is effectively used in classroom learningactivities.Keywords: Modules, Audio Video Repair, and Maintenance Techniques, STAD